컴퓨터 기반 협력학습을 위한 퍼실리테이팅 챗봇 개발 및 사용성 평가 - 정효정(Hyojung Jung); 우상민(Sangmin Woo) (디지털콘텐츠학회논문지, 2021)
이 연구에서는 컴퓨터 기반 협력학습(Computer Supported Collaborative Learning: 이하 CSCL)에서 학습자의 협력활동을 촉진하기 위한 퍼실리테이팅 챗봇을 개발하고 사용성을 평가하는 데 목적이 있다. 퍼실리테이터의 역할, CSCL에서 발생하는 문제에 대한 문헌분석을 통하여, 퍼실리테이팅 챗봇이 CSCL에서 어떠한 지원을 제공할 것인지 규명하였다. CSCL에서 퍼실리테이팅 챗봇의 역할은 교수적 지원, 사회적 지원, 관리적 지원, 기술적 지원이 중요한 요소로 도출되었으며, Python에서 지원하는 discord bot API인 ‘discord.py’ module의 1.3.3 버전을 사용하여 룰 기반의 퍼실리테이팅 챗봇을 개발하였다. 퍼실리테이팅 챗봇에 대한 사용성 평가는 대학생 45명을 대상으로 진행하였으며, 평균 4.42 이상으로 나타났다. 퍼실리테이팅 챗봇 사용경험에 대한 질적 분석 결과 효율적인 협력 활동을 촉진하고, 협력 과정에서의 몰입감을 높이는 데 도움이 된 것으로 나타났다. 향후 명령어 입력, 대화 참여도 정보 제공방식 등에 대한 보완이 필요하며, 실험설계를 통한 성과 분석 연구가 이루어질 필요가 있다. The purpose of this study is to develop a Facilitating-chatbot for promote learners' collaborative activities in Computer Supported Collaborative Learning (CSCL) and to evaluate its usability. Through literature analysis on the role of the facilitator and the problems that occur in CSCL, we identified what kind of support the Facilitating-chatbot will provide in CSCL. In CSCL, the role of the Facilitating-chatbot was derived as important factors for instructional support, social support, administrative support, and technical support. A rule-based Facilitating-chatbot was developed using version 1.3.3 of the ‘discord.py’ module, a discord bot API supported by Python. The usability evaluation of the Facilitating-chatbot was conducted for 45 college students, and the average was 4.42 or higher. As a result of qualitative analysis of the experience of using the Facilitating-chatbot, it was found that it facilitated efficient collaborative activities and helped increase the sense of immersion in the collaborative process. In the future, it is necessary to revise the command input method and the method of providing information on dialogue participation, and it is necessary to conduct research on performance analysis through experimental design. KCI Citation Count: 4